THE EFFECT OF FRYING METHOD ON NUTRITION CONTENT OF FLAXSEED (Linum usitatissimum) AS A POULTRY FEED: EFFECT OF FRYING METHOD ON NUTRITION CONTENT OF FLAXSEED (LINUM USITATISSIMUM) AS A POULTRY FEED (Jurnal Peternakan Nusantara, 2023)
Linum usitatissimum is one of feed ingredients with high protein from the Cerealia group, so it is very potential to be used for bran substitution alternative, but flaxseed contain several antinutrients, like Phytic acid and tannin, it can cause disrupt metabolism and productivity of livestock, so it’s can be reduced by heating with the frying method. The purpose of this research was to determine the effect of frying variance on the nutritional content and antinutrient of flaxseed as a feed due to the treatment given. The analysis used is Analysis of Variance (ANOVA) in Completely Randomized Design (CRD). The results showed that the treatment was able to give a very significant effect (P<0.01) on the content of dry matter, ash, crude protein, crude fiber, crude fat, gross energy, ADF, NDF, as well as anti-nutritional phytic acid and tannins. The frying treatment reduced the dry matter content by 94.99±0.07a, ash 2.93±0.01a, crude protein 20.48±0.07a, crude fat 27.10±0.02a, gross energy 5919.65±10.61a, ADF as much as 27.36±0.05a, NDF as much as 37.22±0.07a, as well as anti-nutritional phytic acid as much as 37.03±0.03a and tannin as much as 1.99±0.0014a, but increased the crude fiber as much as 15.84±0.01d. The best linseed roasted is roasted frying used sand as media with 10 minutes.